Indexing Public Pensions in Progress to Wages or Prices - Simonovits, András (Central European Journal of Economic Modelling and Econometrics, 2020)
Initial public pensions are indexed to the economy-wide average wages, but pensions in progress are indexed to prices, average wages or their combinations – varying across countries and periods. We create a simple overlapping cohorts framework to study the properties of indexing pensions in progress – emphasizing a neglected issue: close wage paths should imply close benefit paths even at real wage shocks. This robustness criterion of an equitable pension system is only satisfied by wage indexing, which in turn requires the adjustment of the accrual rate. To minimize the redistribution from low-earning short-lived citizens to high-earning long-lived ones, progression should be introduced.